Penerapan Analisis Konjoin untuk Mengukur Preferensi Konsumen Minyak Goreng - Marina Herawati; Guntarti Tatik Mulyati; Suharno Suharno (agriTECH, 2002)
Many similar products are offerred by some companies that give consumer's free of choice. Each company has the opprotunity to meet her consumer's need. First of all, company has to understand what product's attributes and the combination of product's attributes. Conjoint analysis can produces the combination which are important in marketing activities. The method of conjoint analysis which is used in this research can produces sttribute combination that is effecting consumer's decision making when they want to buy a product. Result shows the combination of product attributes, such as price, lighteness, colour, flavour and taste, and easiness to acquire, most prefered price of palm oil was under Rp. 5000 per litre, light, yellow to white with weight value of 12.5% and average combination utility value is 2.2632.